Modelling of Heat and Mass Transfer for Wire-Based Additive Manufacturing Using Electric Arc and Concentrated Sources of Energy - Trushnikov, Dmitriy; Perminov, Anatoly; Pang, Shengyong; P. Karunakaran, K.; Belenkiy, Vladimir; Permyakov, Gleb; Kartashov, Maksim; Matveev, Evgeniy; Dushina, Alena; Schitsyn, Yury; ., . (International Journal of Engineering and Technology, 2018)
The paper presents a model developed by the authors and aimed to describe heat and mass transfer during wire-based additive manufacturing, when electron beam, plasma or arc are used as energy sources in case of non-consumable electrode welding. The model describes non-stationary and non-equilibrium conjugated processes of heat and mass transfer in free-surface liquid metal. The solution of differential equations of viscous fluid motion (Navier-Stokes), with convective terms and at laminar flow, has become the model base. Melting and crystallization of the metal is recognized by heat release in a two-phase region. The material density variation during phase transitions of the first and the second order can be described by introducing a certain dependence on temperature. The model is able to consider the use of preliminary and additional induction heating by changing the initial temperature and establishing an additional distributed bulk heat source. Variables for the simulation of heat and mass transfer during additive formation are the intensity and type of the heat source, the plate initial temperature, the power density distribution, the intensity of the additional bulk heating, the dependence of material thermal and physical characteristics on temperature, the characteristics of the phase transitions, the motion velocity of the heat source, the rate of wire feeding.Â